2017
DOI: 10.1016/j.ijbiomac.2017.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Dual crosslinked pectin–alginate network as sustained release hydrophilic matrix for repaglinide

Abstract: Repaglinide, an oral antidiabetic agent, has a rapid onset of action and short half-life of approximately 1h. Developing a controlled and prolonged release delivery system is required to maintain its therapeutic plasma concentration and to eliminate its adverse effects particularly hypoglycemia. The present study aimed to develop controlled release repaglinide loaded beads using sodium alginate and pectin with dual cross-linking for effective control of drug release. The prepared beads were characterized for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…The hydrogel beads obtained at this stage were in the semisolid state. The hydrogel beads were collected and air-dried overnight at 30°C as explained by Awasthi and co-workers [37].…”
Section: Preparation Of Double Crosslinked Portulacaalginate Hydrogelmentioning
confidence: 99%
“…The hydrogel beads obtained at this stage were in the semisolid state. The hydrogel beads were collected and air-dried overnight at 30°C as explained by Awasthi and co-workers [37].…”
Section: Preparation Of Double Crosslinked Portulacaalginate Hydrogelmentioning
confidence: 99%
“…The nature of alginate and pectin were known to be very hydrophilic since they consisted of many -OH and -COOH groups. The presence of divalent cations, such as Ca 2+ , replaced the Na + ions in the sodium alginate and caused the polymer chains of alginate/pectin to cross-link [18]. This process increased the mechanical strength of alginate/pectin film, reducing its dissolution in water; however, it still has the ability to swelling.…”
Section: Characterization Of Alginate/pectin-phenanthroline Filmmentioning
confidence: 99%
“…Pectins are widely used in food industries (food additive E440 according to International Numbering System for Food Additives (INS)) as gelling or thickening agents and in the pharmaceutical industry as bulking agents in drug production, in wound healing preparations, and in medical adhesives for oral drug delivery formulations (e.g., controlled release systems, gastro-retentive systems, colon-specific delivery systems, and mucoadhesive delivery systems). Beads prepared from sodium alginate and pectin with dual cross-linking were tested for effective control of release of the antidiabetic drug repaglinide [18]. Numerous applications have been reported that exploit the colon-specific delivery ability of pectins.…”
Section: Introductionmentioning
confidence: 99%